Self-esteem, job-search intensity and career decision making among graduating universities students - Norida, Abdullah (Faculty of Education, Universiti Teknologi malaysia, 2009)
This study will examine whether there are relationship between self-esteem, job-search intensity and career decision-making among graduating students. This study will also investigate the differences of self-esteem, job-search intensity and career decision-making among students based on gender, ethnicity, academic major, cumulative grade point average (CGPA), socioeconomic status, and residential setting. Mixed methods research design combine quantitative and qualitative approaches will be used. The instruments will be used in this study are a demographic information sheet purposely design for this study, the Rosenberg Self-Esteem Scale (RSES - Rosenberg 1965), Job-Search Intensity Scale (JSIS-Blau 1994), and the Career Decision-Making Self-Efficacy Scale-Short Form (CDMSE-SF; Betz. et al.1996). The population and sample of the study will be consisted of all graduating students in 5 faculties at UTeM, and all graduating students in 3 faculties at UTM, based on 2009/2010 academic session. Participants will be recruited using cluster sampling procedure, also known as multistage sampling. The raw data will be processed using Statistical package of Social Science (SPSS) software. Descriptive statistic, Pearson 's Correlation(r) and two-way ANOVA will be used.